EVALUASI KONSTRUKSI JALAN JALUR LINTAS TIMUR - Mohammad Firdaus Ekamarga; Noor Salim .; Adhitya Surya Manggala (Universitas Muhammadiyah Jember, 2017)
Highways are dirt paths above the earth's surface created with shapes, sizes and types of construction so that they can be used to funnel people, animals and vehicles transporting goods from one place to another easily and quickly (Clarkson H. Oglesby, 1999).The Eastern Lane (JLT) of Lumajang Regency is a road connecting the northern road (Lumajang-Jember road) and the southern road (Lumajang-Kencong road). The road becomes an alternative way for vehicles passing through Lumajang regency without going through the central city route of Lumajang Regency. Road geometric planning is part of a plan that determines the stated dimensions of a path and its parts. From the geometric planning of this road, the road pavement will be carried out. Determination of pavement thickness in accordance with the required highway, also must be adjusted with technical requirements so that the planned road construction is optimal. Road pavement generally includes surface layer, base layer, sub base layer, and subgrade layer. The road pavement is carried out in accordance with the pavement thickness plan according to the age of the plan, or gradually. From the results of the study is expected to be made into planning evaluation with attention to the development of traffic and geometric conditions of roads and road construction conditions that can support the safety and comfort of road users.Keywords: Road Construction Evaluation.